Study of sintered aluminum materials with nanoparticles microadditions. Issue 1 (May 2020) - Agureev, L E; Savushkina, S V; Laptev, I N; Ivanov, B S; Ivanov, A V; Kostikov, V I; Eremeeva, Zh V
Abstract: Sintered aluminum materials with small additions (0.01-0.15 vol.%) of aluminum, zirconium and magnesium oxide nanoparticles were obtained by powder metallurgy. The microstructure of the samples and the effect of the nature and concentration of nanoparticles on the matrix grain size, density, microhardness, and corrosion resistance in 10% solutions of nitric and sulfuric acids were studied. The addition of nanoparticles led to matrix grains decrease, an increase in the density, microhardness, and corrosion resistance of sintered aluminum samples. The lowest value of grain size was shown by the sample with 0.1% vol. magnesium oxide. Sintered aluminum material with 0.05% vol. zirconium oxide nanoparticles had the highest density∼ 2.67 g/cm 3 . The highest Vickers microhardness at the level of 0.474 GPa was obtained for material with the addition of 0.1 vol.% Al2 O3 nanoparticles. All samples showed significantly greater corrosion resistance in comparison with pure sintered aluminum. The samples with nanoparticles withstood 30 hours of testing, and pure aluminum dissolved in nitric acid in 15 hours, and in sulfuric acid in 10.